"Dile que le he escrito un blues" : del texto como partitura a la partitura como traducción en la literatura latinoamericana - Vidal, M. Carmen Africa (Madrid : Iberoamericana ; Frankfurt am Main : Vervuert Verlag, 2017)
This book addresses the interdisciplinarity of translation as a creative activity and its relationship with music in the context of Latin American literature.
Allegro ma non troppo -- Sobre el silencio, los ruidos y los ritmos de la traducción -- A propósito del concepto de equivalencia : Igor Stravinsky y Milan Kundera vs. Jorge Luis Borges y Glenn Gould -- Voces en contrapunto -- Coda : un beso no es un Kiss (por fin, el Blues).
Includes bibliographical references and index.
Online resource; title from PDF title page (Digitalia, viewed October 15, 2019)
Keywords: Translating and interpreting; Music and language; Songs -- Texts -- Translating; Latin American literature -- Translating; Electronic books